Long-chain NHC-stabilized RuNPs as versatile catalysts for one-pot oxidation/hydrogenation reactions. Issue 26 (3rd March 2016) - Martínez-Prieto, L. M.; Ferry, A.; Rakers, L.; Richter, C.; Lecante, P.; Philippot, K.; Chaudret, B.; Glorius, F.
Abstract : The synthesis and catalytic activity of long-chain NHC-stabilized RuNPs are presented. Abstract : The synthesis and catalytic activity of long-chain NHC-stabilized RuNPs are presented. Full characterization of these novel nanostructures including surface state studies show that the ligand influences the number and the location of Ru active sites which impacts the NP catalytic activity, especially in hydrogenation reactions. The high stability and versatility of these nanosystems make them successful catalysts for both oxidation and hydrogenation reactions that can even be performed successively in a one pot-fashion.